2005
DOI: 10.1111/j.1442-2050.2005.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopically guided insertion of self-expandable metal esophageal stents for palliative treatment of patients with malignant stenosis of esophagus and cardia: comparison of uncovered and covered stent types

Abstract: The aim of this retrospective study was to present and compare the results of using two different types of esophageal self-expanding stents (uncovered and covered) for palliative treatment of patients with inoperable malignant stenosis of the esophagus and cardia. Over a period of 8 years, 152 patients underwent fluoroscopically guided insertion of metal esophageal stents. We inserted uncovered esophageal nitinol Strecker stents in 54 patients (group I) and covered esophageal Ultraflex stents in the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 44 publications
3
43
0
1
Order By: Relevance
“…Comparative studies of various types of self-expanding oesophageal stents reported similar rates of efficacy and complications. [175][176][177][178][179][180] Immediate haemorrhage rates are low, but consideration should be given to delayed severe haemorrhage, and this is likely to be a particular risk in patients on APA or anticoagulant therapy.…”
Section: Endoscopic Stent Insertionmentioning
confidence: 99%
“…Comparative studies of various types of self-expanding oesophageal stents reported similar rates of efficacy and complications. [175][176][177][178][179][180] Immediate haemorrhage rates are low, but consideration should be given to delayed severe haemorrhage, and this is likely to be a particular risk in patients on APA or anticoagulant therapy.…”
Section: Endoscopic Stent Insertionmentioning
confidence: 99%
“…The incidence of post-stenting TE fi stula has not been shown to differ between types of stents [2]. In patients in whom TE fi stula occurs, survival from the diagnosis of TE fi stula rarely exceed 30 days [2].…”
Section: Case Reportmentioning
confidence: 99%
“…The incidence of post-stenting TE fi stula has not been shown to differ between types of stents [2]. In patients in whom TE fi stula occurs, survival from the diagnosis of TE fi stula rarely exceed 30 days [2]. Taking the risk of stentrelated complications into consideration, further investigation is needed to identify the risk factors for stent-related TE fi stula to properly select candidates of esophageal stenting for malignant stenosis.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations